Study of Intermolecular Interaction Between Polyacrylonitrile and Amphoteric Surfactant (Betaine) in Dimethylformamide Medium - Abdul Nour, Said (Asian Journal of Chemistry, 2014)
Monomers of polyacrylonitrile were determined by the use of infrared spectroscopy. Viscosity and specific electrical conductivity of polyacrylonitrile were studied in N,N-dimethylformamide medium at different concentrations and temperatures. The critical micelle concentration of amphoteric surfactant (betaine) was determined in N,N-dimethylformamide medium. It was proved that viscosity and conductivity of polyacrylonitrile solutions containing betaine decrease at the field of critical micelle concentration. Crystalline structure of polyacrylonitrile in the solid phase in the presence of betaine was performed by X-ray diffraction and scanning electron microscope, found that betaine contributes in the development of polymer structure.